The geometric concepts of the Istana Dalam Loka traditional house: An ethnomathematics study - Meyundasari, Maulidia Dwi; Hastuti, Intan Dwi; Syaharuddin, Syaharuddin; Mehmood, Saba (Jurnal Elemen, 2024)
This study explores the philosophical aspects of traditional architecture and ethnomathematics geometry in the Istana Dalam Loka traditional house, located in West Nusa Tenggara. Employing a qualitative approach with an ethnographic design, data were gathered through observations and interviews with key, primary, and additional informants. Findings indicate that mathematical concepts are reflected in every architectural element, such as rectangles in doors, terraces, stairs, shields (kantar), kandaga, the sultan's palanquin (tandu), pineapple decoration, and frames. The study also identifies square concepts in the sultan's child's palanquin, glass boxes, and windows. Circular concepts are found in badong, and the concept of an isosceles triangle is present in the roof, offering potential for creative geometry learning. This research has implications in enriching students' mathematical education by utilising geometric examples from local culture. Integrating ethnomathematics into elementary school curricula can broaden students' cultural perspectives, increase student engagement in learning, and enrich students' understanding of mathematics.